TANGIS DI BAWAH LAMPU MERAH: KAJIAN ETIKA KRISTEN TERHADAP EKSPLOITASI ANAK SEBAGAI PERBUDAKAN - Purba, Fredi Ardo; Simangunsong, Dion Carlos (Diegesis : Jurnal Teologi, 2025)
The phenomenon of buskers and car window cleaners at red lights carrying babies to solicit pity is increasingly prevalent in big cities. This practice raises serious issues because it involves the exploitation of children as a means of gaining sympathy with the aim of economic gain. This article examines child exploitation in this context as a form of modern slavery from the perspective of Christian ethics. This research uses a descriptive qualitative approach to analyse this phenomenon through a review of relevant literature. The results show that child exploitation in the form of using babies for begging at red lights can be categorised as a form of modern slavery. Christian ethics condemns this practice because it contradicts human values that recognise every human being as God's creation that is valuable and has dignity. A Christian ethical perspective suggests that any action that treats human beings, especially children, as tools for economic gain is a violation of human dignity and the fundamental rights of the child. The church, as an institution that holds a prophetic role, must be actively involved in responding to this issue, through education, advocacy, and social services to protect children from exploitation.